Being angry, singing fast? Signalling of aggressive motivation by syllable rate in a songbird with slow song - Linhart, Pavel; Jaška, Pavel; Petrusková, Tereza; Petrusek, Adam; Fuchs, Roman (Behavioural processes, 2013)
Syllable rate has been shown to play a role in male-male aggressive interactions and has been proposed to serve as a male quality indicator in several bird species. In those with fast syllable rates, males often increase rates when singing in aggressive context, and respond differently to test stimuli of varying rates. We asked whether the syllable rate fulfils a similar signalling function in the chiffchaff (Phylloscopus collybita), a songbird species with a slow syllable rate. We confronted 36 chiffchaff males with one of three playback types differing in syllable rate: control (non-manipulated rate), fast, or slow (artificially increased and decreased syllable rate, respectively). We recorded tested males' songs and behaviour before and during the experiment. Our results indicate that syllable rate might be an aggressive signal in chiffchaff. Males that physically attacked the loudspeaker during experiments sang faster songs spontaneously, and those that continued singing during the playback responded to fast and non-manipulated stimuli with substantial increase of syllable rate. Indirect evidence further suggests that syllable rate in chiffchaff is unlikely constrained by respiratory demands; thus, we propose that syllable rate in this species functions as a conventional signal of male aggressiveness rather than an index of quality.
Keywords: Syllable rate; Bird song; Vocal performance; vokalizace zvířat; Songbirds; zvířata; zlost; Motivation; Male; Phylloscopus collybita; Playback experiment; Anger; zpěvní ptáci; agrese; Animals; mužské pohlaví; motivace; Aggression; Male–male competition; Vocalization, Animal